2021
DOI: 10.1111/oik.08217
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the trophic niche of an invasive ant explains establishment success and long‐term coexistence

Abstract: Invasive species are one of the main threats to biodiversity worldwide and the processes enabling their establishment and persistence remain poorly understood. In generalist consumers, plasticity in diet and trophic niche may play a crucial role in invasion success. There is growing evidence that invasive ants, in particular, occupy lower trophic levels in their introduced range compared to the native one, but evidences remain fragmented. We conducted stable isotope analysis at five locations distributed on tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…The Hachijojima population was also characterised by a lower trophic level than either Okinawa or Chichijima populations. Shifts to lower trophic levels have been reported in the invasive range of L. humile [ 27 ] and S. invicta [ 28 ], while invasive populations of Formica paralugubris were both up-shifted and down-shifted compared to native range populations [ 34 ]. Trophic shifts in ants are typically associated with variation in the reliance on carbohydrates obtained from honeydew producing insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hachijojima population was also characterised by a lower trophic level than either Okinawa or Chichijima populations. Shifts to lower trophic levels have been reported in the invasive range of L. humile [ 27 ] and S. invicta [ 28 ], while invasive populations of Formica paralugubris were both up-shifted and down-shifted compared to native range populations [ 34 ]. Trophic shifts in ants are typically associated with variation in the reliance on carbohydrates obtained from honeydew producing insects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on trait plasticity in invasive species have to date have largely focused on well-established populations of major pest species, such as L. humile and S. invicta e.g., [ 24 , 32 , 33 ] and typically compare characteristics between native and invasive ranges. Correspondingly, we have a relatively poor understanding of the characteristics of more cryptic invaders and a relative paucity of information on variation among populations within the invasive range, though see [ 27 , 34 , 35 ]. This information is crucial for effective management of invasive species, as it can facilitate the identification of potential threats before they become established and help develop our understanding of adaptive shifts which may occur during the invasion process.…”
Section: Introductionmentioning
confidence: 99%
“…This common trend stands also for the Argentine ant, although some variability in its trophic position and diet breath has been shown in invasive supercolonies (Tillberg et al 2007;Seko et al 2021). Thus, it is more likely that there is higher plasticity in response to local conditions (as it seems to occur in other invasive ant species; e.g., Balzani et al (2021), and that toxic chemicals do not speci cally increase predation in the invasive range.…”
Section: Discussionmentioning
confidence: 99%
“…On genus or community level, ants were found to change their trophic position, probably as a response to alterations in resource availability (Gibb & Cunningham, 2011). Nevertheless, on the species level, ants seem to maintain a functionally homeostatic stable isotope composition (except for invasive species; Roeder & Kaspari, 2017;Balzani et al, 2021), despite variation in nutrient availabilities (Gibb & Cunningham, 2011;Woodcock et al, 2013;Tanaka et al, 2019). Recently, the question arouse if not all naturally occurring ant species maintain a functionally homeostatic stable isotope composition across the range of ecosystems they inhabit (Tanaka et al, 2019), though a very recent study found evidence of shifting trophic positions in ant species between forests and plantations (Tsang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the visitation of carbohydrate baits exposed in forest is expected to be lower, mainly because of the natural abundance of trophobiotic Cinara Curtis, 1835 aphids on conifers, which offer a consistent and reliable supply of carbohydrates for ants (Domisch et al, 2016). Finally, stable isotope analysis can reveal which ant species occupy higher or lower trophic positions (Feldhaar et al, 2010), even within wood ants (Balzani et al, 2021). For the present system, mound-building red wood ants (Formica s.…”
Section: Introductionmentioning
confidence: 99%